Analisis Usaha Agroindustri Kerajinan Keset Sabut Kelapa (Studi Kasus: Desa Baru Kecamatan Batang Kuis Kabupaten Deli Serdang) - Sukirlan Tobing; Retna Astuti; Endang Sari Simanullang (Jurnal Agriuma, 2020)
The aims to describe the production process carft coco mat, revenue, cost production, benefit analysis and B/C ratio in the village of Baru, Batang Kuis Sub District, Deli Serdang Regency. The method of sampling decision is used census with ten samples. The resultsÂ  showed the craft production of coco mat consist of apart, dry in the sun, sifter, pressing, spinning, weaving and packing. The average of total revenue value is Rp Rp 8.585.000/month, the average of total cost production value is Rp 4.151.610,78/month,Â  the average of total benefit value is Rp 4.433.389,22/month, the value of total average B/C ratio is 1,06, this home industry of carft coco mat can be developed.